1990
DOI: 10.1111/j.1399-3054.1990.tb06741.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the starch content during organogenesis in in vitro cultured Begonia rex stem explants

Abstract: Stem explants, excised from greenhouse‐grown Begonia rex plants, were cultured on basal medium (T. Murashige and F. Skoog, Physiol. Plant. 15: 473–497, 1962) contained in sterile Petri dishes. The medium was supplemented with benzyladenine (0.1 mg 1−1) naphthaleneacetic acid (0.01 mg 1−1) and, according to experimental requirements, with either sucrose (3%) or mannitol (3%). Histochemical and biochemical examination of the starch content of the explant was carried out over several days. There was no starch dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been suggested that mannitol can modify the physical and chemical properties of alginate beads, resulting in mechanical compression damage to shoot apices (Paul et al 2000). In addition, mannitol has been shown to inhibit adventitous shoot formation in B. Rex petiole explants cultured on a SIM (Mangat et al 1990). This inhibition was thought to be due to reduced starch synthesis during the early stages of organogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that mannitol can modify the physical and chemical properties of alginate beads, resulting in mechanical compression damage to shoot apices (Paul et al 2000). In addition, mannitol has been shown to inhibit adventitous shoot formation in B. Rex petiole explants cultured on a SIM (Mangat et al 1990). This inhibition was thought to be due to reduced starch synthesis during the early stages of organogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (Mangat et al 1990;Sulpice et al 2009; Lee and Huang 2013) demonstrated the relationship between the starch granules formation in response to sucrose supplementation to different species in in vitro cultured, and in both organogenesis and somatic embryogenesis morphogenetic routes. Mangat et al (1990) related that during Begonia rex organogenesis, with 3% sucrose supplementation, starch accumulation was observed in the first days of culture, with a maximum in about 4-6 days. These starch granules decreased as the shoots were under development, thus suggesting that starch was used as energy source during in vitro morphogenesis.…”
Section: Chloroplast Ultrastructure Under Light and Dark Conditionsmentioning
confidence: 97%
“…Sucrose is the main carbohydrate supplemented into the culture media and prominently acts as an energy source and osmotic requirement during organogenesis (Verma and Dougall, 1977; Thorpe et al, 1986; Iraqi et al, 2005; Huang et al, 2006; Feng et al, 2010; Silva, 2010). The correlation between starch metabolism and shoot regeneration was also reported in tobacco (Thorpe et al, 1986), sugarcane (Ho and Vasil, 1983), Begonia (Mangat et al, 1990) and rice (Huang et al, 2006). However, little is known about the signals to trigger sucrose metabolism in cultured cells, especially at the gene expression level.…”
Section: Discussionmentioning
confidence: 63%